Zeolite absorption as ammonia filter in waters And the effects on water quality - Hasibuan, Saberina; Pamukas, Niken Ayu; ', Nasrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from March to April 2014, for 30 days in Aquaculture circle Quality Laboratory Unit of Fisheries Faculty and Marine Sciences, University of Riau Pekanbaru. The aims of research was to investigate zeolite absorption toward ammonia and it effects water quality by recirculation system to rear of river catfish (Mystus nemurus). The methods used was experiment with 4 treatment and 3 replications. The treatments were P0= control, P1= Dosis 45,48 g/12 litres atau 3,79 g/litres, P2= Dosis 90,96 g/12 litres atau 7,58 g/litres, dan P= Dosis 136,44 g/12 litres atau 11,37 g/litres. The best treatment is P3, the result show that the more zeolit dose so many ammonia absorption. Water parameters recorded as follows pH (5-6 mg/L ), temp (28,7 – 30,2), DO (3,37- 4,88), Ammonia (P3 0,02-0,54 mg/L), CO2 (0,45 – 10,48).Key Words : River Catfish (Mystus nemurus), recirculation, filter, zeolit, water quality